PENGARUH UMPAN BALIK POSITIF TERHADAP MOTIVASI DAN HASIL BELAJAR PADA MATERI KSP KELAS XI SMA - Putra Ariana, Pandu Eka; Hairida, Hairida; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis background of this study were unsatisfying achievement and lack of motivation. The purpose of this study were 1) to determine whether there was a significant difference of achievement and students? motivation, also to know how big the influence of giving Positive feedback toward the motivation between student taught using positive feedback, and 2) to determine the effect size of positive feedback toward students? achievement and motivationand of Chemistry student grade eleventh SMA Panca Bhakti Pontianak in subject ?Solubility and Solubility Product?. Nonequivalent Control Group Design was applied as of research design. Tools for collecting data used was a test of achievement, questionnaire, interview guidelines, and observation sheet. According to data analysis using spss, probability values were 0.000 and 0.000. which meant if there were significant differences of students? achievement and motivation respectively between experimental and control classes. The Effect Sizes of learning with positive feedback toward students achievement and motivation were 1,1 and 1,2 respectively. These calculation indicated that learning with positive feedback had high effect on students? achievement and motivation. Keywords: Positive Feedback, Learning motivation, Learning result, Solubility and solubility product constant